2015
DOI: 10.3402/gha.v8.29745
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive use and distribution of high-risk births in Nigeria: a sub-national analysis

Abstract: BackgroundFamily planning expansion has been identified as an impetus to harnessing Nigeria's demographic dividend. However, there is a need for data to address pockets of inequality and to better understand cultural and social factors affecting contraceptive use and health benefits. This paper contributes to addressing these needs by providing evidence on the trends and sub-national patterns of modern contraceptive prevalence in Nigeria and the association between contraceptive use and high-risk births in Nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 16 publications
(9 reference statements)
1
22
0
Order By: Relevance
“…Two, grand multiparity is dominant among women in Nigeria. This finding corroborates evidence in a number of previous studies in Nigeria which found the dominance of high parity among Nigerian women [ 37 – 39 , 49 ]. With increasing evidence that grand multiparity remains an obstetric challenge in Nigeria [ 40 – 44 ], it is important that the consequences of grand multiparity for women’s health be brought to the fore of national population policy strategy for improving women’s health and safe motherhood in the country.…”
Section: Discussionsupporting
confidence: 92%
“…Two, grand multiparity is dominant among women in Nigeria. This finding corroborates evidence in a number of previous studies in Nigeria which found the dominance of high parity among Nigerian women [ 37 – 39 , 49 ]. With increasing evidence that grand multiparity remains an obstetric challenge in Nigeria [ 40 – 44 ], it is important that the consequences of grand multiparity for women’s health be brought to the fore of national population policy strategy for improving women’s health and safe motherhood in the country.…”
Section: Discussionsupporting
confidence: 92%
“…Most women in this study had ever or were currently using contraceptives as opposed to the existing evidence that contraceptive uptake has been abysmal in Nigeria [11,[13][14][15]. A plausible reason for the high contraceptive use in this study is the increased awareness campaign of contraceptives among people living with HIV and AIDS.…”
Section: Discussionmentioning
confidence: 78%
“…Hence, many of them are still sexually active. Thirdly, with high unmet need for family planning in several developing countries including Nigeria, there may be likelihood of unintended pregnancies among women of advanced reproductive age [27]. With only 9% of women aged 30–49 years being menopausal in Nigeria, the susceptibility to pregnancy remain high among women in advanced reproductive age [18].…”
Section: Introductionmentioning
confidence: 99%